Demographic, clinical, and laboratory characteristics of children with confirmed Coronavirus disease 2019 (COVID-19) in Bali - Purniti, Ni Putu Siadi; Sidiartha, I Gusti Lanang; Subanada, Ida Bagus; Mayangsari, Ayu Setyorini Mestika; Aryani, I Gusti Ayu Dwi; Adi, I Putu Dwi (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2021)
Introduction: The Coronavirus disease 2019 (COVID-19) has become a global issue since the disease was first reported in Wuhan, China, in December 2019. The proportion of COVID-19 cases in children is less than in adults, with highly variable incidence rates. Milder clinical manifestations occur in children than adults. Children with comorbidities are more likely to develop more severe symptoms and require hospitalization. Monitoring of laboratory results in confirmed cases of COVID-19 is crucial. Methods: This study was a retrospective study on data collected from the Bali Branch of Indonesia Pediatric Society COVID-19 Team and the Bali Provincial Government Health Department, Indonesia, from March 2020 until February 2021. The study population included children aged 0-18 years with laboratory-confirmed COVID-19. Subjects were selected using the total sampling method. Results: During the study period, 3,674 children were confirmed to have COVID-19. In this study, the majority of age was 12-18 years. Nineteen (0.5%) were neonates with a vertical transmission source. The most prevalent source of transmission was living in the same house, which was found in 1,811 cases (49.3%). Out of 181 confirmed cases of COVID-19 treated at Sanglah Hospital, Denpasar, 49 (27.1%) had comorbidities. In 2,701 (73.5%) cases, the subjects were found to be asymptomatic. 652 (17.7%) subjects had fever, 771 (21%) had cough, and only 17 (0.5%) had anosmia. A total of 139 (3.8%) subjects had symptoms of shortness of breath, and only 4 subjects required treatment with a ventilator. Regarding the infection markers, lactate dehydrogenase (LDH), C-reactive protein (CRP), D-dimer, and procalcitonin showed higher levels in the critical group compared to other groups. Conclusion: The highest incidence of COVID-19 occurs in children aged 12-18 years, and the most frequent sources of close contact come from household contacts. Most children who have confirmed COVID-19 have asymptomatic clinical manifestation. The most common clinical manifestation was cough (21%). Increased infection markers such as LDH, CRP, procalcitonin and D-dimer occur in critically ill COVID-19 patients.